2019
DOI: 10.1002/hbm.24760
|View full text |Cite
|
Sign up to set email alerts
|

Neurite orientation dispersion and density imaging (NODDI) and free‐water imaging in Parkinsonism

Abstract: Neurite orientation dispersion and density imaging (NODDI) uses a three‐compartment model to probe brain tissue microstructure, whereas free‐water (FW) imaging models two‐compartments. It is unknown if NODDI detects more disease‐specific effects related to neurodegeneration in Parkinson's disease (PD) and atypical Parkinsonism. We acquired multi‐ and single‐shell diffusion imaging at 3 Tesla across two sites. NODDI (using multi‐shell; isotropic volume [Viso]; intracellular volume [Vic]; orientation dispersion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
85
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 56 publications
17
85
2
1
Order By: Relevance
“…The principal result of this study is a widespread reduction in synaptic density in PSP‐Richardson’s syndrome and amyloid‐negative CBS (which we define as CBD). This accords with postmortem estimates of synaptic loss in PSP and CBD, using synaptophysin immunohistochemistry, 6 imaging of neurite density in PSP, 41 and morphological studies of cortical dendrites in the closely related condition of frontotemporal lobe dementia 42 . Indirect evidence of synaptic loss, from consequential reduction in metabolism, comes from [ 18 F]FDG PET changes in frontal, temporal, and parietal lobes 43‐46 .…”
Section: Discussionsupporting
confidence: 72%
“…The principal result of this study is a widespread reduction in synaptic density in PSP‐Richardson’s syndrome and amyloid‐negative CBS (which we define as CBD). This accords with postmortem estimates of synaptic loss in PSP and CBD, using synaptophysin immunohistochemistry, 6 imaging of neurite density in PSP, 41 and morphological studies of cortical dendrites in the closely related condition of frontotemporal lobe dementia 42 . Indirect evidence of synaptic loss, from consequential reduction in metabolism, comes from [ 18 F]FDG PET changes in frontal, temporal, and parietal lobes 43‐46 .…”
Section: Discussionsupporting
confidence: 72%
“…This extends previous investigations of ODI microstructural change in PSP-RS and CBS/CBD (Mitchell et al, 2019), demonstrating the in vivo coupling of dendritic complexity to presynaptic density, in line with preclinical models of tauopathies (Hoffmann et al, 2014;Rocher et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, reduced FA partially points to axonal disorganization and degeneration. 16,34 A previous study also identified anatomical connectivity deficits in the basal ganglia−motor cortex pathway, which was consistent with our results and jointly illustrated the degeneration of the basal ganglia−motor cortex pathway. 35 The negative correlations between MD as well as AD in the left nigrostriatal−nigropallidal pathway and FA in the left basal ganglia−motor cortex pathway indicate that the higher diffusivity in the nigrostriatal−nigropallidal pathway, the lower the fiber coherence in the basal ganglia −motor cortex pathway.…”
Section: Degeneration Of Motor Pathways In Parkinson's Diseasesupporting
confidence: 92%